(untitled) (Eurasian Journal of Philology Science and Education, 2019)
This article is the first to describe the features of the emergence of a variety art in nomadic society; it provides the stages of development of musical variety art in Kazakhstan; it reveals general regularities, genre and style characteristics. The article is the first to analyze ways of overcoming ideological taboos of the socialist society in the former Soviet Republic, extending the living space of the traditional music on stage, opening new forms of its existence. This was possible due to transition to an open democratic society with its dynamism, expansion of cultural horizons, availability of world experience. The article describes the birth and development of Kazakh variety art from the 30ies of ХХ century up to the present times, connection of variety art with traditional music and changing ideological paradigms of the Soviet period and the period of independence. The article is devoted to the Kazakh variety art as the main type of art in the republic.